Semantics and Linguocultural Characteristics of Some Uzbek Lexemes - Kadirova Barno Raimovna (International Journal on Integrated Education, 2022)
At a time when international relations are developing and interaction is intensifying, the study of languages and cultures of different nations remains one of the urgent tasks. By the end of the twentieth century, linguistics had assumed that "language is not only connected with culture, but also a means by which it has grown out of culture and expressed it." At the same time, language plays an important role in the creation, development and preservation of culture (in the form of texts). Today in the world the priority role of language in knowing the world, its active influence on the real being, consciousness, is recognized as the main factor and the main source in all spiritual and cognitive activity of the person, this fact forms a solid basis of anthropocentric approach to language. The anthropocentric approach to language has been interpreted in almost all of the research and educational literature on linguoculturology, although it has been interpreted as re-emerging in the late twentieth and early twenty-first centuries. it is emphasized that the background goes back to Humboldt’s famous ideas. V. von Humboldt said, "The diversity of languages is not only due to differences in sounds and signs, but also because of differences in the way we see the world." V. Humboldt's idea that "language is a mirror of culture" reflects the essence of the field of linguoculturology. The article discusses the social function of the language, its role in society, cultural concepts, national values, traditions. Discusses the linguistic and cultural features of the Turkic languages, in particular Uzbek. The semantics of individual lexical units during the period of the ancient Uzbek literary language, linguistic and cultural capabilities, their importance in expressing national values and views are described. In addition to the denotative value in the lexical units of the lifestyle of the Uzbek people, the reflection of the concepts of human relations is explained by typical examples. Emphasizes the need to respect the national language, to consider it as a means of communication and as a reality that collects and expresses national values